2022
DOI: 10.3390/antiox11091750
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of 25-Hydroxyvitamin D3 Improves Growth Performance, Antioxidant Capacity and Immune Function in Weaned Piglets

Abstract: This study was conducted to evaluate the effects of 25-hydroxyvitamin D3 (25(OH)VD3) and Vitamin D3 (VD3) supplemented in the diet of weaned piglets on their growth performance, bone quality, intestinal integrity, immune function and antioxidant capacity. A total of 192 weaned piglets were allocated into four groups and they were fed a control diet containing 2000 IU VD3 (negative control, NC), NC + 100 ppm colistin sulfate (positive control, PC), NC + 2000 IU VD3 (VD3) and NC + 2000 IU 25(OH)VD3 (25(OH)VD3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 68 publications
1
0
1
Order By: Relevance
“…The mean relative contents of fecal SCFAs and p values were presented in Supplementary Table S4 between the two groups. It has been reported that acetic acid, propionic acid, and butyric acid have the dominant content among SCFAs, accounting for more than 85%, 31 , 32 which is consistent with our findings that these three substances constituted most of the SCFAs contents. Then, we focused on the three SCFAs.…”
Section: Resultssupporting
confidence: 93%
“…The mean relative contents of fecal SCFAs and p values were presented in Supplementary Table S4 between the two groups. It has been reported that acetic acid, propionic acid, and butyric acid have the dominant content among SCFAs, accounting for more than 85%, 31 , 32 which is consistent with our findings that these three substances constituted most of the SCFAs contents. Then, we focused on the three SCFAs.…”
Section: Resultssupporting
confidence: 93%
“…In addition, the alpha and beta diversity of the cecal microbial communities were not significantly affected by dietary VD 3 . This finding was inconsistent with a study conducted in weaned piglets, which suggested that dietary VD 3 significantly affected the colon microbial beta diversity [50]. This might have been caused by species differences (broilers vs. piglets), tissue differences (cecum vs. colon), or the supplementation level of VD 3 in the LC group might have been insufficient to cause significant changes in the cecal microbial composition and structure of the tested broilers.…”
Section: Discussioncontrasting
confidence: 73%